2020
DOI: 10.1080/15548627.2020.1771858
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of intra-lysosome pH in cell lines and primary neuronal culture using a novel genetically encoded biosensor

Abstract: Disorders of lysosomal physiology have increasingly been found to underlie the pathology of a rapidly growing cast of neurodevelopmental disorders and sporadic diseases of aging. One cardinal aspect of lysosomal (dys)function is lysosomal acidification in which defects trigger lysosomal stress signaling and defects in proteolytic capacity. We have developed a genetically encoded ratiometric probe to measure lysosomal pH coupled with a purification tag to efficiently purify lysosomes for both proteomic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 106 publications
(119 reference statements)
3
52
0
Order By: Relevance
“…We would like to acknowledge that recently, two related sensors containing mCherry-pHluorin-LAMP1 (Ponsford et al, 2020) and sfGFP-LAMP1-mCherry fusions (Webb et al, 2020) have been published. The described probes have a reported pKa of ~6.5 and ~5.0, 20 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to acknowledge that recently, two related sensors containing mCherry-pHluorin-LAMP1 (Ponsford et al, 2020) and sfGFP-LAMP1-mCherry fusions (Webb et al, 2020) have been published. The described probes have a reported pKa of ~6.5 and ~5.0, 20 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Using pH-dependent properties, pHluorin was also utilized in various studies to measure the pH of organelles such as lysosomes and the endoplasmic reticulum (Reifenrath and Boles 2018). pHluorin also measures autophagy flux as autophagosomes are fused to acidic lysosomes to form autophagolysosomes during the autophagy process (Oliva Trejo et al 2020), and pHluorin measures lysosome acidity that is required for protease activity in living cells (Ponsford et al 2020). pHluorin fused to optogenetic probes measures changes in pH in organelles in response to optogenetic acidification (Rost et al 2015).…”
Section: Ph-sensitive Optical Probesmentioning
confidence: 99%
“…Moreover, in at least one study, it has been reported that the peripheral pool of lysosomes is less acidic and less accessible to biosynthetic cargo (such as cathepsins) (Johnson et al, 2016). However, a subsequent report has shown that peripheral and perinuclear lysosomes have a similar pH (~ 4.4) (Ponsford et al, 2020).…”
Section: Depletion Of Rufy3 Reduces Lysosome Sizementioning
confidence: 99%